(untitled) (Conferencea, 2022)
In the first half of the year 2021, the number of family divorces in Uzbekistan increased by 34% compared to the same period in 2020. Approximately 20,000 families have divorced since the beginning of the year. The highest divorce rates are recorded in Tashkent. In January-June 2021, there were 19,407 divorces in the country. For comparison, this figure was 12.8 thousand in the corresponding period of 2020 or 16 thousand in the same period of 2019 [1]. In a global ranking, Uzbekistan takes a place at least below 50 counties [2].